Respostas

  • Usuário do Brainly
2013-02-19T10:52:35-03:00

Temos que:

 

\text{x}^2+4\text{x}-3=0

 

\text{x}=\dfrac{-4\pm\sqrt{4^2-4\cdot1\cdot(-3)}}{2\cdot1}=\dfrac{-4\pm\sqrt{28}}{2}

 

\text{x}'=\dfrac{-4+2\sqrt{7}}{2}=-2+\sqrt{7}

 

\text{x}''=\dfrac{-4-2\sqrt{7}}{2}=-2-\sqrt{7}

 

\text{S}=\{-2-\sqrt{7}, -2+\sqrt{7}\}

 

Temos que:

 

\text{x}^2+3\text{x}-4=0

 

\text{x}=\dfrac{-3\pm\sqrt{3^2-4\cdot1\cdot(-4)}}{2\cdot1}=\dfrac{-3\pm\sqrt{25}}{2}

 

\text{x}'=\dfrac{-3+5}{2}=1

 

\text{x}''=\dfrac{-3-5}{2}=-4

 

\text{S}=\{-4, 1\}

2 3 2